Synthesis of 0.75Pb(Zr0.52Ti0.48)O3-0.25BiFeO3 Thin Film Capacitors with Excellent Efficiency and Thermal Stability - Li Wu; Feifei Han; Kaiyuan Chen; Jianming Deng; Laijun Liu; Biaolin Peng (Molecules)
The advancement of miniaturizing electronic information technology draws growing interest in dielectric capacitors due to their high-power density and rapid charge/discharge capabilities. The sol-gel method was utilized to fabricate the 0.75Pb(Zr0.52Ti0.48)O3-0.25BiFeO3 (PZT-25BFO) thin film. Excitingly, PZT-25BFO thin film exhibits an exceptional capacitive energy storage density (Wrec = 24.61–39.76 J/cm3) and a high efficiency (η = 53.78–72.74%). Furthermore, the dielectric energy storage density and efficiency enhance simultaneously with increasing thickness of the thin film. However, the loss factor shows the opposite trend. Specifically, the 12-layer PZT-25BFO thin film demonstrates the optimal properties, boasting a significant energy storage density (15.73 J/cm3), a high efficiency (77.65%), and remarkable thermal stability (±0.55% variation) from 303 K to 383 K at 1000 kV/cm. This excellent thermal stability can be attributed to the residual stress resulting from a phase transition from the rhombohedral to tetragonal phase. The result offers valuable guidance for the development of ferroelectric thin films in high-power capacitive energy storage applications.